Social equity in the Asia-Pacific region conceptualizations and realities - Johansen, Morgen (Palgrave Macmillan, 2019)
This book examines the concept and public service value of social equity in public administration research and practice outside of the Western context, considering the influence that historical, cultural, and social trends of Asian and Pacific societies may have on how social equity is conceptualized and realized in the Asia-Pacific region. The book presents the results of an effort by a group of scholars from seven countries (Australia, China, Hong Kong, Japan, Korea, The Philippines, and Singapore), one American State (the Hawaiian Islands), and the Pacific Islands to discover what social equity means in their respective contexts. It concludes by synthesizing and analyzing the chapter authors' findings to advance a more global conceptualization of social equity.-- Provided by publisher.